2019
DOI: 10.18632/aging.102209
|View full text |Cite|
|
Sign up to set email alerts
|

LAV-BPIFB4 associates with reduced frailty in humans and its transfer prevents frailty progression in old mice

Abstract: Background: There is an increasing concern about age-related frailty because of the growing number of elderly people in the general population. The Longevity-Associated Variant (LAV) of the human BPIFB4 gene was found to correct endothelial dysfunction, one of the mechanisms underlying frailty, in aging mice whereas the RV-BPIFB4 variant induced opposite effects. Thus, we newly hypothesize that, besides being associated with life expectancy, BPIFB4 polymorphisms can predict frailty.Aim and Results: Here we inv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 18 publications
(26 citation statements)
references
References 35 publications
3
23
0
Order By: Relevance
“…In line with these findings, circulating BPIFB4 levels were closely linked with the health status of long-living individuals [ 165 ]. Interestingly, LAV-BPIFB4 gene transfer decelerated frailty progression in aged mice and homozygous LAV-BPIFB4 haplotype inversely correlated with frailty in elderly subjects [ 166 ].…”
Section: Behind the Scenes Of Cardiovascular Agingmentioning
confidence: 99%
“…In line with these findings, circulating BPIFB4 levels were closely linked with the health status of long-living individuals [ 165 ]. Interestingly, LAV-BPIFB4 gene transfer decelerated frailty progression in aged mice and homozygous LAV-BPIFB4 haplotype inversely correlated with frailty in elderly subjects [ 166 ].…”
Section: Behind the Scenes Of Cardiovascular Agingmentioning
confidence: 99%
“…First, BPIFB4 has been shown to preserve cellular homeostasis through the activation of many heat shock protein (HSP) family members involved in maintaining and restoring favorable proteostatis 20,21 , which is progressively lost during aging and in neurodegenerative disease. Indeed LAV-BPIFB4 associates with reduced frailty in humans and its transfer prevents frailty progression in old mice 22 .…”
Section: Introductionmentioning
confidence: 99%
“…At the time of recruitment, subjects resulted 51% non-frail and 49% frail. Subsequently, genotyping for BPIFB4 haplotypes has been performed and the association analysis showed that carriers for LAV-BPIFB4 homozygous are underrepresented in the frails, as opposed to RV-BPIFB4 haplotype which is more frequent in the frail subjects [ 37 ].…”
Section: Bpifb4 As a New Genetic Marker Of Frailtymentioning
confidence: 99%
“…To validate the association of the BPIFB4 genotype with the fragile phenotype at a functional level, a further study was conducted on adult and elderly mice in which LAV-BPIFB4 was administered as gene therapy. Interestingly, attenuation of clinical frailty has been reported following treatment with LAV-BPIFB4 in elderly mice [ 37 ]. This work, for the first time, has associated clinical evidence with experimental results whereby a gene haplotype may influence frailty.…”
Section: Bpifb4 As a New Genetic Marker Of Frailtymentioning
confidence: 99%